الصعوبات التي يواجهها طلاب الفصل الدراسي الثاني في ترجمة الأفعال المربةة من اللغة الإنجليزية إلى اللغة العربية: دارسة حالة: قسم الترجمة، كلية اللغات، جامعة بنغازي - Mohsen Aleskandarani, Fouzia (مجلة كلية الاداب, 2024)
The current study has shed light on the translation of English phrasal verbs into Arabic which is considered to be one of the most challenging areas for learners. Phrasal verbs play a crucial role in comprehending and interacting with native speakers since they are commonly utilized in both written and spoken language. Therefore, the objectives of this study is to investigate the difficulties encountered by second semester students at the Faculty of Languages (Translation Department), University of Benghazi, in translating English phrasal verbs into Arabic. The study was carried out in order to find out why the students are unable to translate English phrasal verbs into Arabic correctly. Moreover, it attempted to reveal how does this difficulty affect their quality of translation. Thus, a test consists of twenty sentences that contain phrasal verbs was distributed to the 45 participants to be translated from English into Arabic. Then, participants were interviewed to ascertain the reason beyond the challenges of translating phrasal verbs. The results were analyzed after the data had been acquired; they are represented as scores and percentages. The findings have shown that second semester students are not able to translate English phrasal verbs into Arabic properly, using the wrong translation techinque; the literal one, or due to their reliance on the context which could be a helpful or a misleading means in achieving the correct translation. They also show that learners tend to rely on the context which is not always helpful as they translate them literally, and this makes their translation unacceptable. The study suggested that students should learn phrasal verbs in context and memorize the most common ones by heart.